2010
DOI: 10.1002/path.2672
|View full text |Cite
|
Sign up to set email alerts
|

K‐ras exon 4A has a tumour suppressor effect on carcinogen‐induced murine colonic adenoma formation

Abstract: K-ras encodes two isoforms, K-ras 4A and 4B, that are jointly affected by K-ras activating mutations, which are prevalent in colorectal cancer (CRC). CRC shows alterations in the expressed K-ras 4A : 4B isoform ratio in favour of K-ras 4B, in tumours both with and without K-ras mutations. The present study evaluated whether K-ras 4A expression can suppress colonic adenoma development in the absence of its oncogenic allele. Mice with homozygous targeted deletions of K-ras exon 4A (K-ras(tmDelta4A/tmDelta4A)) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 35 publications
2
43
0
Order By: Relevance
“…injection (25). Similarly, when colonic adenomas were induced in these mice by treatment with 1,2-dimethylhydrazine, mice lacking K-Ras4A had an increase in number and size of colonic adenomas that revealed increased markers of proliferation and decreased markers of apoptosis (26), suggesting that, despite the highly counterintuitive nature of these findings, WT K-Ras4A can behave like a tumor suppressor. However, a similar study using a mouse genetic model to induce colon carcinomas showed no such effect of K-Ras4A deficiency (27).…”
Section: Discussionmentioning
confidence: 90%
“…injection (25). Similarly, when colonic adenomas were induced in these mice by treatment with 1,2-dimethylhydrazine, mice lacking K-Ras4A had an increase in number and size of colonic adenomas that revealed increased markers of proliferation and decreased markers of apoptosis (26), suggesting that, despite the highly counterintuitive nature of these findings, WT K-Ras4A can behave like a tumor suppressor. However, a similar study using a mouse genetic model to induce colon carcinomas showed no such effect of K-Ras4A deficiency (27).…”
Section: Discussionmentioning
confidence: 90%
“…previous studies have shown that expression of mutant K-ras Val12 in either mouse embryonic stem (es) cells or mutant K-ras transgenic mice was associated with changes in expression of a range of gene transcripts and proteins, including stem cell associated genes and components of the Mapk and Akt pathway genes (10,18,(20)(21)(22). Quantitative rt-pcr and immunohistochemical expression analysis of the intestinal tumours Val12 has been shown to stimulate Wnt signaling in colonic cancer through inhibition of GSK-3β (32), which is regulated by the activation of the pI3K/Akt pathway.…”
Section: Discussionmentioning
confidence: 99%
“…the pMApK Family rabbit mAb sampler Kit and the pAKt pathway sampler Kit (cell signaling, usA) were used for MApK and AKt pathway protein analysis by Western blotting. Immunohistochemical analysis was performed with the goat anti-gastrin polyclonal antibody (santa cruz Biotechnology, usA), the rabbit anti-cox-2 monoclonal antibody and the rabbit anti-vascular endothelial growth factor (VegF) polyclonal antibody (both from novus Biologicals, usA) as described previously (21,22).…”
Section: Val12mentioning
confidence: 99%
See 2 more Smart Citations